Exploring mitochondrial health and transplantation strategies in DCD heart transplantation: a systematic review - Xiaoxue Zhang; Yujie Yang; Huan Wang; Chenxi Yan; Yi Feng; Xiantao Ma; Min Hu; Shiliang Li; Cai Cheng (Journal of Translational Medicine)
Abstract This review explores the significant potential of mitochondrial transplantation (MT) in enhancing outcomes for DCD heart transplantation, particularly in mitigating ischemia-reperfusion injury (IRI). MT restores mitochondrial function and ATP production, thereby improving myocardial contractility and counteracting the energy depletion and oxidative stress that jeopardize the viability of DCD grafts. Furthermore, the synergistic application of MT with extracorporeal perfusion significantly enhances graft viability by reducing metabolic waste accumulation and modulating the inflammatory response during prolonged preservation. Studies show that MT decreases reactive oxygen species (ROS) levels, enhances antioxidant enzyme activity, and regulates immune activation, ultimately improving graft survival. Notably, MT has shown promising results in maintaining heart function during extended perfusion, delaying functional loss due to energy depletion. Despite encouraging preclinical findings, additional clinical validation is required, particularly in DCD heart transplantation, to confirm its potential in improving long-term graft function and expanding the donor pool in high-risk scenarios.